KONSEP RESPONSIBLE TOURISM MARKETING (RTM) DALAM MEMBANGUN PARIWISATA - Sofiyani, Kiki; Widyastuti, Nurprapti; Kurniawati, Rd. Nia Kania (JOURNAL OF SCIENTIFIC COMMUNICATION (JSC), 2023)
Indonesia's tourism sector is one of the contributors to increasing the country's foreign exchange, including in employment. Based on a report from the Ministry of Tourism and Creative Economy (2019), the contribution of the tourism sector to Gross Domestic Product (GDP) reached 4.80% and absorbed up to 13 million workers. This impact is not only positive but also negative. One of the negative impacts of tourism include; the tendency of the community to be very high towards tourism, increasing inflation and selling prices of land, there is income inequality between community groups and causing local people to lose control of economic resources (Ismayanti, 2010). This condition also refers to Indonesia's abundant natural wealth, but it is very unfortunate that most human actors tend to prioritize their own social interests (self-interest). Tourism marketing is responsible for integrating the principles of sustainability as the main basis for making marketing decisions. Thus, the principles of sustainability must be included in all tourism marketing decisions, including the creation of tourism products, advertising campaigns, and as an effort to attract and maintain tourist loyalty, various marketing activities must be carried out. The existence of these principles will accelerate the process of improving the tourism sector by creating a positive image, adding advertising, and promoting sales that can increase the number of visits by local and international tourists.Key words : tourism, sustainability, marketing decisions, loyalty